Cost and management accounting : a modern approach - Burch, John G. (St. Paul, MN : West, 1994)
The management accountant's role in modern organizations. Cost accounting systems. Cost management systems. Profit management systems. Investment management systems.
Keywords: Accounting; Finance; Economics; Managerial accounting; Cost accounting